2016
DOI: 10.1002/btpr.2351
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydrofolate increases suspension growth of dihydrofolate reductase‐deficient chinese hamster ovary DG44 cells in chemically defined media

Abstract: Adaptation of dihydrofolate reductase (DHFR)-deficient Chinese hamster ovary (CHO) DG44 cells to chemically defined suspension culture conditions is a time-consuming and labor-intensive process because nonadapted DHFR-deficient CHO DG44 cells normally show poor growth in chemically defined medium (CDM). We examined the effects of folate derivatives, ribonucleotides, and nucleobases on the growth of suspension-adapted DHFR-deficient CHO DG44 cells in CDM. Among the tested additives, tetrahydrofolate (THF) was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Tetrahydrofolate (THF), the active form of folate (vitamin B9), is an essential cofactor of one-carbon (1C) cycle and involved in the biosynthesis of thymidylate, purines, and glycine [23,24]. Previous researches have delineated that THF is susceptible to oxidative stress and exhibits a high antioxidant activity when excessive level of ROS cumulation is available [25,26], implying that THF might be a candidate for ameliorating surplus ROS to enhance rehabilitative capacity of NSC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrahydrofolate (THF), the active form of folate (vitamin B9), is an essential cofactor of one-carbon (1C) cycle and involved in the biosynthesis of thymidylate, purines, and glycine [23,24]. Previous researches have delineated that THF is susceptible to oxidative stress and exhibits a high antioxidant activity when excessive level of ROS cumulation is available [25,26], implying that THF might be a candidate for ameliorating surplus ROS to enhance rehabilitative capacity of NSC.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, previous study has demonstrated that the THF transporter of SLC25A32 is highly expressed in varying tumors, and obviously facilitated tumor cell growth to reduce patients' survival, whereas downregulation of SLC25A32 inhibits tumor cell propagation [27]. Moreover, THF administration is an effective intervention in promoting proliferation of dihydrofolate reductase-(DHFR-) deficient Chinese hamster ovary (CHO) DG44 cells [24], while the effect of THF on NSC proliferation and the underlying mechanism remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%